Silver, Hoards and Containers - The archaeological and historical context of Viking - Age silver coin deposits in the Baltic c. 800-1050 - Gruszczynski, J (University of Oxford, 2018)
This is version 1 of a catalogue designed to accompany ‘Silver, Hoards and Containers’ published by Taylor- Francis/Routledge (Gruszczynski 2018), which has been derived from a DPhil thesis defended at the University of Oxford in December 2016 and written within the remit of the AHRC-funded ‘Dirhams for Slaves’ project, based at the Khalili Research Centre, University of Oxford. In this catalogue, a hoard is understood as find of at least two silver artefacts discovered at a single place and time as a form of material wealth which was disposed of deliberately for reasons known and important to the hoarder (after von Brunn 1968:236). The hoards detailed below fulfil three criteria dictated by the research questions and analytical methodology applied in ‘Silver, Hoards and Containers’ (cf. Gruszczynski 2018, Chapter 1): • comprise coins, which provide fairly secure dating to c.800-1050; • which location can be determined with reasonable precision; and • where the weight of silver is known or could be reconstructed statistically. Version 2 of this data is available at https://doi.org/10.5287/bodleian:KOqjpvvQn Version 1 of a catalogue of silver hoards containing coins from Gotland, Pomerania and Svealand (cf. Gruszczynski 2018) dated to c. 800-1050